Nervonic acid limits weight gain in a mouse model of diet‐induced obesity. Issue 11 (22nd September 2020) - Keppley, Laura J. W.; Walker, Susan J.; Gademsey, Alexis N.; Smith, Jason P.; Keller, Susanna R.; Kester, Mark; Fox, Todd E.
Abstract: Lipid perturbations contribute to detrimental outcomes in obesity. We previously demonstrated that nervonic acid, a C24:1 ω‐9 fatty acid, predominantly acylated to sphingolipids, including ceramides, are selectively reduced in a mouse model of obesity. It is currently unknown if deficiency of nervonic acid‐sphingolipid metabolites contribute to complications of obesity. Mice were fed a standard diet, a high fat diet, or these diets supplemented isocalorically with nervonic acid. The primary objective was to determine if dietary nervonic acid content alters the metabolic phenotype in mice fed a high fat diet. Furthermore, we investigated if nervonic acid alters markers of impaired fatty acid oxidation in the liver. We observed that a nervonic acid‐enriched isocaloric diet reduced weight gain and adiposity in mice fed a high fat diet. The nervonic acid enrichment led to increased C24:1‐ceramides and improved several metabolic parameters including blood glucose levels, and insulin and glucose tolerance. Mechanistically, nervonic acid supplementation increased PPARα and PGC1α expression and improved the acylcarnitine profile in liver. These alterations indicate improved energy metabolism through increased β‐oxidation of fatty acids. Taken together, increasing dietary nervonic acid improves metabolic parameters in mice fed a high fat diet. Strategies that prevent deficiency of, or restore, nervonic acid may represent an effective strategy to treat obesity and obesity‐related complications.